Lafaz Al-Hubb dalam Al-Qur’an menurut Al-Buthi - Muslim Djuned (TAFSE: Journal of Qur'anic Studies, 2023)
Love is a feeling that has moved human life. It is often defined as an expression of affection and sympathy towards a specific object. Due to the sacredness of love in life, the Quran has mentioned it in several verses, both explicitly and implicitly. These verses have been uniformly understood by scholars, but Said Ramadhan al-Buthi has a unique and different perspective in interpreting them. Therefore, this research focuses on how al-Buthi interprets al-hubb (love) that is found in several verses in the Quran and then classifies them. This research aims to uncover the meaning of love in the Quran according to al-Buthi and what thematic categorization he does on love in the Quran. This research is a literature review (library research). Furthermore, the data is analyzed by descriptive analysis. The results show that al-Buthi defines love as a feeling of attachment to something where a person feels comfortable when close to the object and reluctant to be away from it. However, this definition is only applicable to humans. For him, the illustration of Allah's love is difficult to explain in detail because Allah is not like His creatures, but recognition of Allah's love can be achieved through the path that Allah has set. Furthermore, al-Buthi classifies love in the Quran into several categories, namely: Allah's love for humans and the impact of that love in increasing human obedience, then human love for Allah, which is divided into al-hubb al-kasbi and al-hubb al-qadim.Abstrak: Al-Qur’an dalam beberapa ayat menyinggung tentang cinta baik secara tersurat maupun tersirat. Ayat-ayat tersebut kemudian dipahami secara seragam oleh para ulama, namun Said Ramadhan al-Buthi memiliki pandangan yang unik dan berbeda dalam memahami ayat-ayat tersebut. Untuk itu, penelitian ini menekankan pada bagaimana al-Buthi memaknai al-hubb yang terdapat dalam beberapa ayat dalam Alquran dan kemudian mengklasifikasikannya. Penelitian ini bertujuan untuk menyingkap makna al-hubb dalam Alquran menurut al-Buthi dan apa saja klasifikasi yang ia lakukan terhadap al-hubb dalam Alquran. Penelitian ini bersifat kepustakaan (library research). Selanjutnya data dianalisis dengan cara analisis deskriptif. Adapun hasil penelitian menunjukkan bahwa al-Buthi mendefinisikan cinta sebagai suatu perasaan keterikatan terhadap sesuatu dimana seseorang merasa nyaman ketika berdekatan dengan sang objek serta merasa enggan untuk jauh darinya. Namun definisi tersebut hanya layak disematkan kepada manusia, baginya pengilustrasian cinta Allah merupakan sesuatu yang sulit dijelaskan secara gamblang, karena Allah tidaklah serupa dengan makhlukNya, namun pengenalan terhadap cinta Allah dapat dicapai melalui jalan yang telah Allah tetapkan. Selanjutnya al-Buthi mengklasifikasikan al-hubb dalam Alquran menjadi beberapa klasifikasi, yaitu: cinta Allah kepada manusia beserta dampak dari cinta tersebut berupa bertambahnya ketaatan manusia, kemudian cinta manusia kepada Allah yang terbagi kepada al-hubb al-kasbi dan al-hubb al-qadim.